Marine pharmacognosy : - Kim, Se-Kwon (Taylor & Francis, 2013)
"Marine pharmacognosy is a dynamic field that has been systematically investigated over the last 50 years. The potential of the field is shown by the number of publications and the patents that are constantly increasing every year. This book presents the latest comprehensive studies of marine derived medicinal substances for biological, medical and industrial applications. Marine flora and fauna has been the source of molecules used as pharmaceuticals, cosmeceuticals, nutraceuticals, molecular probes, fine chemicals and agrochemicals. Bringing together a global author team of experts, this text provides a current snapshot of the importance of marine products in health formulation"--Provided by publisher.